2013
DOI: 10.1111/1567-1364.12028
|View full text |Cite
|
Sign up to set email alerts
|

Isobutanol production fromd-xylose by recombinantSaccharomyces cerevisiae

Abstract: Simultaneous overexpression of an optimized, cytosolically localized valine biosynthesis pathway together with overexpression of xylose isomerase XylA from Clostridium phytofermentans, transaldolase Tal1 and xylulokinase Xks1 enabled recombinant Saccharomyces cerevisiae cells to complement the valine auxotrophy of ilv2,3,5 triple deletion mutants for growth on D-xylose as the sole carbon source. Moreover, after additional overexpression of ketoacid decarboxylase Aro10 and alcohol dehydrogenase Adh2, the cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 11 publications
0
36
0
Order By: Relevance
“…However, prior studies reported contrary results to this expectation. No meaningful improvements in the production of 2,3-butanediol [142] and isobutanol [143] which are derived from pyruvate have been reported under xylose conditions. A notable difference between the enhanced lactic acid production and the latter ineffectual production of 2,3-butanediol and isobutanol is the order of metabolic engineering efforts.…”
Section: Production Of Advanced Biofuels and Chemicals From Xylose Bymentioning
confidence: 99%
“…However, prior studies reported contrary results to this expectation. No meaningful improvements in the production of 2,3-butanediol [142] and isobutanol [143] which are derived from pyruvate have been reported under xylose conditions. A notable difference between the enhanced lactic acid production and the latter ineffectual production of 2,3-butanediol and isobutanol is the order of metabolic engineering efforts.…”
Section: Production Of Advanced Biofuels and Chemicals From Xylose Bymentioning
confidence: 99%
“…However, these processes are highly dependent on the purity of the waste stream and face several challenges before being scaled up. Biological approaches being developed include production of PHB (polyhydroxybutyrate), a feedstock for the production of bioplastics (Garcez Lopes et al 2011); and biofuels, such as ethanol, isobutanol and triacylglycerol (TAG) (Brat & Boles 2013;Kurosawa et al 2013;Q. Li et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We focused our attention on the strategy which takes advantage of ketoacids as intermediates in amino acids biosynthesis and degradation metabolism to produce fusel alcohols in the yeast S. cerevisiae . While the pathway to isoketovalerate was better elucidated and recently successfully exploited for isobutanol formation in S. cerevisiae [13-17], butanol production from ketovalerate was never experimentally measured.…”
Section: Introductionmentioning
confidence: 99%